Penerapan Pendekatan Sains-lingkungan-teknologi-masyarakat (STM) untuk Meningkatkan Kemampuan Siswa SD dalam Mengaplikasikan Konsep Keseimbangan Lingkungan - Sri Estu Winahyu; Harti Kartini (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2008)
Abstract: The purpose of this collaborative action research is to describe the improvement  students competencies in applying a concept of environmental balance through the STM approach. The subjects was Sixth grade students of the VI Madyopuro Elementary School. The collected data were acquired through observation and interview. The collected data were analyzed by qualitative and path model. The results found: STM approach changed  students’ conception about influence human action on environmental balance; improvement students’ competency in applying concept; improvement students’ critical thinking.